PENGGUNAAN ONLINE LEARNING PADA MATAKULIAH HERMENEUTIKA AL QURAN (STUDI TERHADAP MAHASISWA SEMESTER VI STAI AL ANWAR SARANG REMBANG) - Luthfil Hakim; Husniyatus Salamah Zainiyati (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
This study aims to examine online learning as a medium and innovation in active learning learning. Through this research it can be seen that online learning is distance learning that uses electronic circuits and is carried out through the internet media to convey learning content, interactions or guidance with teaching materials that suit the needs. The dynamics that occur in the digital era also function as a catalyst for the learning system revolution from what was previously manual and conventional to an effective and efficient system with the support of information and communication technology (ICT). The method used in this research is a case study with a research approach using qualitative methods that are used to obtain information in the form of interview data and documentation about the use of online learning in al-Quran hermeneutics courses on semester VI students of STAI Al-Anwar Sarang Rembang.